The Impacts of Inclusion in Clinical Trials on Outcomes among Patients with Metastatic Breast Cancer (MBC). - Ji Yun Lee; Sung Hee Lim; Min-Young Lee; Hae Su Kim; Jin Seok Ahn; Young-Hyuck Im; Yeon Hee Park (PLoS ONE, 2016)
BACKGROUND:Metastatic breast cancer (MBC) remains a devastating and incurable disease. Over the past decade, the implementation of clinical trials both with and without molecular targeted therapeutics has impacted the daily clinical treatment of patients with MBC. In this study, we determine whether including MBC patients in clinical trials affects clinical outcomes. METHODS:We retrospectively reviewed data for a total of 863 patients diagnosed with initial or recurrent (after receiving adjuvant systemic treatments following surgery) metastatic disease between January 2000 and December 2013. Data were obtained from the breast cancer database of Samsung Medical Center. RESULTS:Among the 806 patients selected for inclusion, 188 (23%) had participated in clinical trials. A total of 185 clinical trials were conducted from 2000 to 2014. When compared with earlier periods (n = 10 for 2000-2004), clinical trial enrollment significantly increased over time (n = 103 for 2005-2009, P = 0.024; n = 110 for 2010-2014, P = 0.046). Multivariate analyses revealed that biologic subtype, distant recurrence free interval (DRFI), and clinical trial enrollment were independent predictors of overall survival. Patients who participated in clinical trials showed improved survival, with a hazard ratio of 0.75 (95% CI, 0.59-0.95), which was associated with a 25% reduction in the risk of death. However, subgroup analysis showed that this improved survival benefit was not maintained in patients with triple negative breast cancer (TNBC). CONCLUSIONS:Although not conclusive, we could speculate that there were differences in the use of newer agents or regimens over time, and these differences appear to be associated with improved survival.